2009
DOI: 10.1097/ccm.0b013e31819598f5
|View full text |Cite
|
Sign up to set email alerts
|

Antishock effect of anisodamine involves a novel pathway for activating α7 nicotinic acetylcholine receptor*

Abstract: These findings demonstrate that the antishock effect of anisodamine is intimately linked to alpha7nAChR-dependent anti-inflammatory pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 27 publications
4
58
0
Order By: Relevance
“…In cardiovascular system, the α7nAChR was reported as an important protector in myocardial ischemia/reperfusion injury [9], stroke [10], atherosclerosis [11] and hypertension [12,13]. Our group previously showed that activation of α7nAChR protects against lipopolysaccharide-induced septic shock via inhibiting release of inflammatory cytokines [14]. We also demonstrated that downregulation of α7nAChR might contribute to the development of end organ damage through inducing cardiovascular inflammation in both genetic and experimental hypertension [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In cardiovascular system, the α7nAChR was reported as an important protector in myocardial ischemia/reperfusion injury [9], stroke [10], atherosclerosis [11] and hypertension [12,13]. Our group previously showed that activation of α7nAChR protects against lipopolysaccharide-induced septic shock via inhibiting release of inflammatory cytokines [14]. We also demonstrated that downregulation of α7nAChR might contribute to the development of end organ damage through inducing cardiovascular inflammation in both genetic and experimental hypertension [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanisms of these effects remain unclear [4,5] . Recently, a study conducted in this laboratory demonstrated that the anti-shock effects of anisodamine occur mainly via activation of the α7 nicotinic acetylcholine receptor (α7nAChR) [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that anisodamine blocks muscarinic receptors and promotes increased endogenous acetylcholine binding to the α7nAChR [6] .…”
Section: Introductionmentioning
confidence: 99%
“…10 The anti-inflammatory actions of vagal efferent activity appear to be mediated chiefly by acetylcholine (ACh) acting at the ␣7 nicotinic acetylcholine receptor (␣7nAChR). 11,[13][14][15] The vesicular acetylcholine transporter (VAChT) mediates the loading of ACh into secretory organelles in neurons, thereby making ACh available for release. 16,17 Thus, if impairment of cholinergic antiinflammatory pathways contributes to development of EOD during hypertension, then dysfunction of the ␣7nAChR and/or the VAChT seems likely.…”
mentioning
confidence: 99%